Meta-modes of learning that support and influence the millennial student’s holistic learning experience at an academic institute in South Africa - de Swardt, M.; Hoque, M.E. (South African Journal of Higher Education, 2018)
Teaching in diverse ways to a diverse generation, globally, academic institutes must ensure that learning is responsive, appropriate and supportive of cohorts in emerging and involving modes of learning. However, the pedagogy, processes and learning methods are of paramount importance for this diverse student generation in order to recognise subsequent cohorts for whom motivation and engagement in a holistic learning experience for millennial students could be maximised. While it has been recognised that current learning practices may not address the holistic learning experience of the millennial student, the purpose of this study, through the adoption of the Student-Owned Learning-Engagement (SOLE) model, its nine elements and 42 meta-modes of learning, is to investigate and identify the confluence of meta-modes of learning that could support and influence the millennial student’s holistic learning experience. In response to the needs of aspiring millennial learners, data were obtained from 69 students and 15 teachers by means of a self-administrated questionnaire. A comparison was drawn between the theories that the millennials preferred meta-modes of learning and the modes of teaching that the teachers had adopted. Hence, this study offers strategies to improve the holistic experience of learning. This is performed in a manner that support new empirical emerging and involving modes of learning for the millennial student.